Girl giant and the jade war - Hoàng, Văn (Roaring Brook Press, 2021)
"Thom Ngoh thought the Monkey King was her friend--he taught her to control her super strength and to stand up for herself. But really he was just using her. He tricked her into stealing from the Heavens and releasing him from his 500-year prison. Now the Monkey King is waging a war against the Heavens and Thom must do everything in her power to fix the mess she made. Determined to prevent a war, Thom and her dragon friend Kha set off on an adventure across the Heavens to search for allies. But with the stakes higher than ever, the price for help may be more than Thom is willing to pay"--Provided by publisher.